Dell's SupportAssist customer adoption model: enhancing the next generation of data‐intensive support services. (13th March 2018) - Ghaffarzadegan, Navid; Rad, Armin A.; Xu, Ran; Middlebrooks, Sam E.; Mostafavi, Sarah; Shepherd, Michael; Chambers, Landon; Boyum, Todd
Abstract: We developed a decision support system to model, analyze, and improve market adoption of Dell's SupportAssist program. SupportAssist is a proactive and preventive support service capability that can monitor system operations data from all connected Dell devices around the world and predict impending failures in those devices. Performance of such data‐intensive services is highly interconnected with market adoption: service performance depends on the richness of the customer database, which is influenced by customer adoption that in turn depends on customer satisfaction and service performance—a reinforcing feedback loop. We developed the SupportAssist adoption model (SAAM). SAAM utilizes various data sources and modeling techniques, particularly system dynamics, to analyze market response under different strategies. Dell anticipates improving market adoption of SupportAssist and revenue from support services, as results of using this analytical tool. Copyright © 2018 The Authors System Dynamics Review published by John Wiley & Sons Ltd on behalf of System Dynamics Society